G182(P) Systematic review of infant and young children complementary feeding practices in south asian families: The developed countries perspective. (24th May 2017) - Manikam, L; Amadi, C; Robinson, A; Stephenson, L; Shafi, T; Lever, I; Ahmed, S; Lingam, R; Lakhanpaul, M
Abstract : Background: Sub-optimal nutrition among children remains a significant problem in South Asian (SA) families across the world and is related to micronutrient deficiencies, obesity and dental caries. The optimisation of complementary feeding practices (CFP) in the first two years of life is vital in tackling these issues. Aims: To undertake a systematic review of studies assessing CFP, timing, dietary diversity, and influencing factors in children under two years of age in SA in developed countries (DC). Methods: We searched Medline, Embase, Global Health, Web of Science, OVID Maternity and Infant Care, Cochrane Library, Popline, and WHO Global Health Library from January 1st 1990 to June 30th 2016. Eligibility criteria were all primary research studies on CFP in SA children aged 0–2 years, their families, or both, restricted to the English language. Search terms were 'children', 'feeding', and 'Asians' with their derivatives. Study selection, data extraction, and quality appraisal (EPPI-Centre weight of evidence) were performed by two independent researchers in a narrative synthesis approach. Results: From 45 712 studies screened, 860 full-text articles were assessed for eligibility with 135 included in the synthesis. 10 studies from developed countries (UK, USA and Australia) were finally extracted. Despite adopting the WHO Infant and Young Children Feeding (WHO IYCF) guidelines, sub-optimal CFP were found in all studies. In 3 of 4 studies which addressed timing, CF was introduced before 6 months; and was not introduced between 6–12 months in any study despite recommendations. Coverage of The Pregnancy Book and Birth to Five ranged from 94% among Caucasian mothers but fell to 68%–88% among SA mothers. Dietary diversity was inadequate in 6 of 7 studies which discussed it with sweet convenience foods commonly used. Factors affecting practices included: acculturation, socioeconomics and conflicting sources and content of information. Conclusions: This is the first systematic review to evaluate complementary feeding practices in SA across DC. In comparing the findings to those from reviews assessing developing countries, similar sub-optimal practices were noted between families from both types of countries despite ratification of WHO IYCF guidelines. This review will contribute towards informing future intervention development.